Isolamento, caracterização molecular e avaliação da toxicidade de Bacillus thuringiensis Berliner, 1911 do Cerrado Maranhense em larvas de Aedes aegypti (Linnaeus, 1762) (Diptera, Culicidae) - Lobo, Katiane dos Santos (2015)
Currently dengue is a serious global public health problem, in Brazil there is increase in the number of cases every year and the circulation of several serotypes. The development of new strategies for the control of Aedes aegypti is of utmost importance to minimize or eliminate the cases of the disease. An alternative for the control of this vector is the use of biological control agents such as Bacillus thuringiensis, which is toxic to this insect order of epidemiological importance. In this study, we sought to investigate the biological control of A. aegypti, with the use of B. thuringiensis isolated from Cerrado Maranhense. Selective bioassays were conducted to determine the entomopathogenic activity against the larvae of A. aegypti, quantitative bioassays in order to determine the toxicity of isolates, by means of the estimation of Median Lethal Concentration (LC50) and PCR tests (Polymerase Chain Reaction) to verify the presence of mosquitocidal genes (cry and cyt). From 45 soil samples collected in 17 counties in the State, it was obtained 1225 bacterial colonies, with 383 (31.26%) identified as B. thuringiensis. Of the 383 isolates tested, 12 (3.13%) showed larvicidal activity greater than 50% (BtMA 25, BtMA 64, BtMA 104, BtMA 131, BtMA 194, BtMA 251, BtMA 401, BtMA 410, BtMA 413, BtMA 450, BtMA 451 and BtMA 560), which were selected for subsequent realization of the quantitative bioassay and molecular characterization. The quantitative bioassays allowed to observe that the lower LC50 values were obtained with the isolate 401 (4.0 x 104 spore-crystals/mL) and with the standard bacteria Bti (0.32 x 107 spore-crystals/mL). The others tested isolates showed low larvicidal activity. The PCR analysis showed that from eight tested genes: cry4Aa, cry4Ba, cry10Aa, cry11Aa, cry11Ba, cyt1Aa, cyt1Ab and cyt2Aa, five of them: cry11Aa, cry11Ba, cyt1Aa, cyt1Ab and cyt2Aa were detected in ten isolates, being absent in only two of 12 isolates tested. These data demonstrate that the isolates of B. thuringiensis from Cerrado Maranhense showed high pathogenicity and potential for biological control of A. aegypti.